Susceptibility analysis of desertification in the basin of river headland - Pernambuco – Brazil - dos Santos Ferreira, Pedro; Marcos dos Santos, Antonio; Mayron Santana Ferreira, Johnny; dos Santos Ferreira, Henrique; Domiciano Galvício, Josiclêda (Investigaciones Geográficas, 2017)
The current economic development model adopted by society, based on consumption, has drawn the attention of environmentalists due to the strong pressure that it has exerted on natural environments. This pressure has resulted in serious problems of environmental order. Among them, desertification emerges as the major challenge to be faced. Desertification is understood as a process of degradation of arid, semi-arid, and dry sub-humid lands, resulting from climatic variations and from the impact of human activities. In this sense, the aim of this paper is to analyze the degree of susceptibility to desertification of the river basin of Pontal. For the mapping of susceptibility to desertification, we extrapolated georeferenced data such as land use and land cover, soils, slope, erosion potential of rain and aridity index. Overall the basin presented low susceptibility to desertification, and the removal of vegetation cover was identified as the main responsible for the appearance of high susceptibility areas. Due to the great economic importance of the Pontal basin, because of expansion of irrigated areas, this research proposes that further studies need to be developed in order to find viable alternatives to the desertification combat.